2001
DOI: 10.1097/00007890-200104150-00017
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic Immune Modulation Prevents Acute Rejection but Not the Development of Graft Arteriosclerosis (Chronic Rejection)1

Abstract: Intrathymic immune modulation does not abolish alloreactivity, and despite induction of long-lasting graft survival, this procedure does not prevent and may even facilitate the development of GAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…1A and Table 1). These findings are consistent with our previous studies [39] and a recent study demonstrating that intrathymic immune modulation with allogeneic cells prevented acute but not chronic rejection [20]. Allografts with delayed rejection (1 5-82 days; IZ = 6) showed dense mononuclear cell infil- tration, moderate-to-severe myocardial fibrosis, severe vascular proliferative lesions, and lesions related to acute episodes of allograft rejection, such as vasculitis, interstitial hemorrhage, and myocardial necrosis (Fig.…”
Section: Intrathymic Immune Modulation With Class-i Allopeptides Doessupporting
confidence: 92%
“…1A and Table 1). These findings are consistent with our previous studies [39] and a recent study demonstrating that intrathymic immune modulation with allogeneic cells prevented acute but not chronic rejection [20]. Allografts with delayed rejection (1 5-82 days; IZ = 6) showed dense mononuclear cell infil- tration, moderate-to-severe myocardial fibrosis, severe vascular proliferative lesions, and lesions related to acute episodes of allograft rejection, such as vasculitis, interstitial hemorrhage, and myocardial necrosis (Fig.…”
Section: Intrathymic Immune Modulation With Class-i Allopeptides Doessupporting
confidence: 92%
“…Recently, we reported that after intrathymic immune modulation the intragraft cytokine profile in long-term allografts (>200 days) has shifted from a Th1 type (high IL-2 and IFN-γ) toward a Th3 or Tr1 type (high IFN-γ, TGF-β, and IL-10; no IL-2) profile. This altered immune response might preserve graft endothelium, but it does not prevent the development of TA (30). Studying human kidney biopsies, Lagaaij et al recently suggested a correlation between the degree of EC replacement by recipient-derived endothelium and the severity of vascular rejection (16).…”
Section: Discussionmentioning
confidence: 99%
“…CsA (Sandoz Pharma AG, Basel, Switzerland) was injected intramuscularly on days 1, 2, and 3 after transplantation (15 mg/kg). Cardiac allografts thus transplanted show significantly prolonged graft survival but eventually develop TA indicative of CTD (30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations